2015
DOI: 10.1111/ijd.12855
|View full text |Cite
|
Sign up to set email alerts
|

The clinicopathological spectrum of trichoepitheliomas: a retrospective descriptive study

Abstract: The current study was confined to a cohort of patients, in the Western Cape Province of South Africa, whose ethnic and geographic origins were not available. The extrapolation of findings from this study to the rest of the South African population may not be valid. A cribriform growth pattern occurs in the majority of cases of multiple TEs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…4 Most TEs are sporadic and solitary tumors in younger patients; however, less commonly, they can be a manifestation of Brooke-Spiegler syndrome, associated with germline mutations in the tumor suppressor gene CYLD. 44,45 Histologically, TB is a large, circumscribed dermal tumor without epidermal connection, composed of small basaloid cells arrayed in numerous large nodules or micronodules (Figure 3, A). [46][47][48] Similarly, TE is a well-circumscribed dermal tumor consisting of nests and strands of basaloid cells in a racemiform configuration.…”
Section: Benign Hair-germ Tumors (Trichoepithelioma Andmentioning
confidence: 99%
“…4 Most TEs are sporadic and solitary tumors in younger patients; however, less commonly, they can be a manifestation of Brooke-Spiegler syndrome, associated with germline mutations in the tumor suppressor gene CYLD. 44,45 Histologically, TB is a large, circumscribed dermal tumor without epidermal connection, composed of small basaloid cells arrayed in numerous large nodules or micronodules (Figure 3, A). [46][47][48] Similarly, TE is a well-circumscribed dermal tumor consisting of nests and strands of basaloid cells in a racemiform configuration.…”
Section: Benign Hair-germ Tumors (Trichoepithelioma Andmentioning
confidence: 99%
“…In fact, CYLD is involved in the regulation of biological processes such as cell proliferation and inflammation, and loss of the deubiquitinating activity of CYLD protein has been correlated with tumorigenesis (Liang et al 2005;Nagy et al 2015). Therefore, the awareness of the potential development of carcinoma in patients carrying CYLD mutations is important (du Toit et al 2016;Kallam et al 2016). Consequently, guidance on photoprotection was provided to all study participants.…”
Section: Discussionmentioning
confidence: 99%
“…They are considered small if less than 2 centimeters in diameter or giant if greater than 2 centimeters. Reports of giant solitary trichoepitheliomas comment that they are usually pedunculated, up to several centimeters in diameter, and found on the head, perianal region, and thighs of adults [1]. They arise in adults in the 7th decade and must be differentiated from basal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the reported cases in the literature discussed patients of Fitzpatrick skin type IV-VI with lesions involving the face. du Toit et al reported a South African patient with a linear trichoepithelioma on the nasal dorsum and Chang reported an African-American female with unilateral configuration of trichoepitheliomas on the left nasolabial fold and left cheek following the lines of Blaschko [1,5]. Geffner et al reported a 10 year old African American female who presented with extensive linear grouped papules on the left shoulder, left anterior and posterior trunk, and left lower extremity that were found to be trichoepitheliomas [6].…”
Section: Discussionmentioning
confidence: 99%